2011
DOI: 10.1089/tmj.2010.0189
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Differently Priced Devices for Digital Capture of X-Ray Films Using Computed Tomography as a Gold Standard: A Multireader-Multicase Receiver Operating Characteristic Curve Study

Abstract: Objective: Film digitizers are a specialized technology that is available for scanning X-ray radiographs; however, their cost makes them unaffordable for developing countries. Thus, less expensive alternatives are used. The purpose of this study was to compare three devices for digital capture of X-ray films: a film digitizer (US $15,000), a flatbed scanner (US $1800), and a 10-megapixel digital camera (US $450), in terms of diagnostic accuracy, defined as the area under the receiver operating characteristic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Evaluation of the same devices [21] in a clinical ROC curve statistical study did not find statistical significant differences in diagnostic accuracy. However, this study was more expensive and time-consuming: The study length was 8 months and included six radiologists, with a factorial design that required 2,448 observations which were analyzed through receiver operating characteristic curves [22,23] and statistical analysis of variance [24], which are highly complex epidemiological and statistical models to perform.…”
Section: Discussionmentioning
confidence: 80%
“…Evaluation of the same devices [21] in a clinical ROC curve statistical study did not find statistical significant differences in diagnostic accuracy. However, this study was more expensive and time-consuming: The study length was 8 months and included six radiologists, with a factorial design that required 2,448 observations which were analyzed through receiver operating characteristic curves [22,23] and statistical analysis of variance [24], which are highly complex epidemiological and statistical models to perform.…”
Section: Discussionmentioning
confidence: 80%
“…This methodology has been tested on one only hardware: also flat-bed scanners and film digitizers could be considered; however other authors demonstrated how the here-used acquisition set up performs similarly to the others, having the advantage of being less expensive [9,10] . The last aspect is significant, considering minor healthcare centres which could take benefit from teleradiology implementation [20] .…”
Section: Resultsmentioning
confidence: 99%
“…An important evolution came in the seventies when radiographs have started to be acquired by means of a video-camera [7] , and successively with the advent of solid-state slide or image scanners, until nowadays when digitised radiographs are directly available. Nevertheless x ray film digitisation remains necessary when retrospective analysed are being performed [8] or electronic archives are being built, or for implementing tele-radiology in places where conventional radiology is still used routinely as in rural healthcare centres of the developing world [9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High quality digital images of radiographs preserve diagnostic quality compared to the original hard copies [4][5][6] and are comparable to more expensive flatbed scanners and film digitizers [7]. More recent studies have shown that even smartphone camera pictures of radiographs are of sufficient quality for detection of the presence or absence of major abnormalities, and frequently allow for a specific diagnosis [8].…”
Section: Introductionmentioning
confidence: 99%